The Impact of Direct Cash Payments on Whole Blood Supply. Issue 4 (9th August 2019) - Becker, David M.; Klüter, Harald; Niessen‐Ruenzi, Alexandra; Weber, Martin
Abstract: This paper investigates the impact of monetary incentives on whole blood donations. We take advantage of a quasi‐natural experiment in Germany, in which one blood donation site changes its payment scheme from remunerated to non‐remunerated. All other donation sites maintain their payment schemes. We show that donation volumes drop significantly after the pay drop and do not recuperate. At the same time, donation volumes increase at other paid donation sites, which is partly due to donor migration to these sites. We do not find any impact of the changed payment scheme on blood quality. Our results offer additional insight into the complex question whether it is efficient to ensure blood supply by paying donors a direct monetary compensation.